Influence of Financial Compensation on Employee Performance at PT. Bank BTPN, Padang City - Weni Yuliani; Lisa Hendriani; Novendra Halim (Smart International Management Journal, 2024)
Subtle skills relate to each person's ability to communicate and behave with others. These abilities include the ability to communicate, provide a variety of solution options, and decide on the best solution (Melati, 2023). This is the method that PT BANK BTPN Kota Padang needs to get a workforce that can help the growth and progress of the company. Based on the previous background, the author tries to examine how to improve compensation in labor management that can help the operations of PT BANK BTPN Kota Padang. The author examines this problem with the title "The Effect of Financial Compensation on Employee Performance". This research uses the case study method to collect data and obtain the necessary information. This research also collected data by making direct visits to the research location and reading a number of books and scientific articles related to the issues discussed. Since Ho is rejected and Ha is accepted, the results show that compensation (X) has a significant impact on employee performance. It is suspected that compensation affects the performance of employees of PT Bank Btpn Kota Padang. This hypothesis is accepted as there is a positive correlation between employees' compensation and their performance at work. The PT Bank BTPN Kota Padang workers' financial pay has a big impact on how well they work. This suggests that workers are more likely to be driven and committed to completing their tasks when they believe their pay is commensurate with the amount they provide